Sleep patterns in 1 to 36 month-old children - Catharina Sambo; Rini Sekartini; Partini Trihono (Paediatrica Indonesiana, 2010)
Background Better understanding about sleep patterns inIndonesian children can contribute to basic knowledge foreducating parents and health providers about good sleephygiene.Objectives To find out sleep patterns in 1ô€Š36 monthô€Šoldchildren.Method A descriptive, crossô€Šsectional study was held in EastJakarta on May 2009. Subjects were 1 to 36 months old childrenwho came \\lith their parents or primary caregivers. Data collectionwas performed using modified Brief Infant Sleep Questionnaire(BISQ), consisted of subjects' characteristics, sleep patterns, sleepproblems, and associating factors.Results Among 147 children, sleep problems were identified in33.3% of them. Bedtime was mostly at 8 p.m., wake up time was5 a.m. Median time needed to fall asleep was 20 minutes. Averagefrequency of night waking was twice during one night. Mediannight waking duration was 15 minutes. Median sleep duration atnight was 9 hours 20 minutes, and median nap duration was 2hours 20 minutes. Median total sleep time was 12 hours. Pronesleeping position was significantly associated \\lith sleep problems(pô€‹0.036, RRô€‹1.67, 95%CIô€‹1.66-2.64).Conclusions Prevalence of sleep problem is 33.3%, \\lith awakeningat night was being the most occurring problem. Prone sleepingposition is associated \\lith sleep problems. [Paediatr Indones.2010;50:170-5].